Corporate Social Responsibility Disclosure in Primary Industry: Effect of Risk, Gender, and Environmental Disclosure - Wahdan Arum Inawati; Aulia Fatiha Kurniadi (Owner : Riset dan Jurnal Akuntansi, 2023)
Corporate Social Responsibility (CSR) is one of responsibility to shareholders by paying attention to social and environmental aspect in the vicinity where the company’s operational activities are carried out. However, not all companies which has a direct impact to environment did CSR properly. PT. Aneka Tambang, Tbk. in 2021 was polluting the coast of East Halmahera, endangered mangrove and marine ecosystems. In addition, PT. Vale Indonesia, Tbk. also suspected of being the cause of forest destruction in South Sulawesi which resulted in sedimentation in Lake Mahalona, CSR implementation will impact to CSR disclosure of company. This study aimed to analyze how risk minimization, gender diversity and environmental certification affect CSR disclosure. Researcher used quantitative method. The population in this study were primary industrial companies with 45 observation data after selecting sample used purposive sampling, Researcher chose descriptive and panel data regression analysis using Eviews 12 as analysis method. The results of this study indicate that risk minimization, gender diversity, and environmental certification have a simultaneous effect on CSR. Partially, risk minimization has a negative effect on CSR disclosure. Meanwhile, gender diversity and environmental certification have no effect on CSR disclosure. Adjusted R-square in this study was 12,43%. It indicated that independent variable used in this study effect dependent study in 12,43%, remained 87,57% effected by other independent variable outside study.